REPORT OF PRACTICAL CLASS IN AGRICULTURAL AREA WITH THE BACHELOR CLASS IN AGRONOMY IN THE MUNICIPALITY OF TRACUATEUA-PA: A PEDAGOGICAL PROPOSAL IN THE DISCIPLINE OF INDUSTRIAL CROPS I - Clifferson da Silva Matos, Giovani (2024)
Cassava (Manihot esculenta Crantz) is a highly consumed root and a significant source of carbohydrates in Brazil and around the world. In the state of Pará, cassava is vital to the local economy, especially in the municipality of Tracuateua. The culture involves family farmers and serves as an important source of income and subsistence. Different cultivars are used, such as BRS Tapioqueira and BRS Verdinha, which exceed 70 thousand kg/ha with good management. Adequate fertilization, pest control and weed management are essential for high productivity. Irrigation can significantly increase production. On the property of Mr. Benedito Dutra, member of the RENIVA project, the production of seed cassava and cowpea is highlighted. It uses cultivars developed by Embrapa, such as BRS Kiriris, BRS Formosa and BRS Novo Horizonte, which are recommended for industrial use. Dutra also grows cowpeas, using varieties such as BRS Guirá and BRS Natalina, which are highly productive and adapted to local conditions. The property has an irrigated area of ​​23 hectares per central pivot, ensuring crop hydration during dry periods. During the field visit, several areas of experimentation were observed. The experimental plots of cassava and cowpea showed good performance, with a high survival rate and resistance to pests. The integration of advanced soil management, pest control and irrigation practices highlighted the property as an example of innovative agriculture. The experience on Mr. Dutra’s property demonstrated the importance of innovation and adoption of advanced agricultural practices for sustainable and productive agricultural production.